EDUKASI PENERAPAN K3 PADA KARYAWAN DI PKS PT. CISADANE SAWIT RAYA NEGERI LAMA TAHUN 2024 - Tampubolon, Elmina; Sembiring, Johannes (INSTITUT KESEHATAN DELI HUSADA, 2025)
The implementation of an effective Occupational Safety and Health (K3) system in all work units, including plantations and palm oil mills (PKS), is very important because it has a direct impact on employee productivity. Therefore, education on the implementation of K3 at PKS Negeri Lama still needs to be carried out as a preventive measure in dealing with work accidents.This activity was held on February 15, 2025, at the PT. Cisadane Sawit Raya Negeri Lama PKS, using a seminar method and aids in the form of picture booklets and leaflets containing information on the implementation of K3 in the workplace. Participants were employees directly involved in high-risk work and exposed to work environment conditions.The results of the activity showed an increase in understanding of the implementation of K3 among employees, namely 83.3%. In addition, from the results of observations and discussions from the PkM team with employees of PT. Cisadane Sawit Raya Negeri Lama, it was also found that: 1) The level of work risk between divisions is different so that the company needs to pay special attention to divisions with high risks so that the implementation of K3 is more targeted; 2) This activity received a positive response from employees, which indicates that awareness of the importance of implementing K3 in the work environment among employees will increase; and 3) support from the company is needed so that an efficient and sustainable work system is created.